2020
DOI: 10.1158/1541-7786.mcr-20-0359
|View full text |Cite
|
Sign up to set email alerts
|

Role of TET1 and 5hmC in an Obesity-Linked Pathway Driving Cancer Stem Cells in Triple-Negative Breast Cancer

Abstract: Triple-negative breast cancer (TNBC) is a subtype of breast cancer that lacks expression of estrogen receptor, progesterone receptor, and the HER2 but is enriched with cancer stem celllike cells (CSC). CSCs are the fraction of cancer cells recognized as the source of primary malignant tumors that also give rise to metastatic recurrence. 5-Hydroxymethylcytosine (5hmC) is a DNA epigenetic feature derived from 5-methylcytosine by action of tet methylcytosine dioxygenase enzymes (e.g., TET1); and although TET1 and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(51 citation statements)
references
References 50 publications
2
49
0
Order By: Relevance
“…This study opens a new avenue for TNBC treatment by targeting the EZH2-H3K27me3-TET1 pathway, which can modulate the epigenetic landscape. In 2020, Bin Bao et al [ 51 ] demonstrated that TET1- and TET1-dependent 5hmC mediated a novel hydrogen peroxide-(H 2 O 2 )-dependent gene expression cascade response driving the self-renewal and expansion of cancer stem cell-like cells (CSCs) in TNBC.…”
Section: Tet1 In Clinical Diseasementioning
confidence: 99%
“…This study opens a new avenue for TNBC treatment by targeting the EZH2-H3K27me3-TET1 pathway, which can modulate the epigenetic landscape. In 2020, Bin Bao et al [ 51 ] demonstrated that TET1- and TET1-dependent 5hmC mediated a novel hydrogen peroxide-(H 2 O 2 )-dependent gene expression cascade response driving the self-renewal and expansion of cancer stem cell-like cells (CSCs) in TNBC.…”
Section: Tet1 In Clinical Diseasementioning
confidence: 99%
“…Subsequently, methyl-CpG-binding domain protein 2, variant 2 (MBD2_v2), is activated, and finally maintains CSC self-renewal. Furthermore, obesity increases levels of pro-inflammatory signaling factors, such as cytokines, which increase the H 2 O 2 level in breast cancer cells [ 155 ].…”
Section: Epigenetic Regulation In Breast Cancer and Bcscsmentioning
confidence: 99%
“…TET1 expression was demonstrated to promote cell metastasis in colorectal cancer and activation of PI3K oncogenic signaling in TNBC. TET1 expression was shown to correlate with cell migration, cancer stemness tumorigenicity, and poor survivals in epithelial ovarian cancer and in TNBCs [ 77 , 78 , 79 ].…”
Section: Are Tet Enzymes Tumor-suppressors or Oncogenes?mentioning
confidence: 99%
“…In another study that supports the oncogenic role of TET1, it was shown that TET1-mediated hypomethylation upregulated gene expressions that drove self-renewal and expansion of cancer stem cells in TNBC. This TET1-mediated oncogenic function is an alternate mechanism that was shown to be due to the downregulation of the catalase enzyme which increases the hydrogen peroxide levels, or be due to exogenous routes such as systemic inflammation and oxidative stress within the context of obesity in TNBC [ 77 ].…”
Section: Are Tet Enzymes Tumor-suppressors or Oncogenes?mentioning
confidence: 99%